EVA composite foamed material and preparation method thereof

By preparing EVA composite foam materials, the problems of insufficient mechanical properties and UV stability of EVA foam materials during processing were solved, and the overall performance and stability of the materials were improved.

CN123026850APending Publication Date: 2026-11-03FUJIAN PROVINCE JINJIANG CITY HUAYIN SHOE MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611542510.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-10-07
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing EVA foam materials produce scraps with poor mechanical properties during processing, including poor elongation at break and compression set, as well as insufficient UV stability, which limits the efficiency of product use.

Method used

The preparation method of EVA composite foam material involves mixing EVA, ethylene-octene copolymer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer, low-density polyethylene, EVA foam waste powder, foaming agent, crosslinking agent and functional additives, graphene modifier, etc. in an internal mixer, followed by open mixing and foaming molding, and static curing to obtain EVA composite foam material.

Benefits of technology

It improves the mechanical properties, elongation at break, and compression set of the material, while enhancing the UV stability of the product and optimizing the functional coordination and stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of EVA foaming, in particular to an EVA composite foaming material and a preparation method thereof, which comprises the following steps: weighing raw materials according to weight parts; feeding EVA, ethylene-octene copolymer, EPDM, hydrogenated styrene-butadiene-styrene block copolymer, low-density polyethylene, EVA foaming waste powder, a functional additive, a graphene modifier, zinc stearate and stearic acid into a banbury mixer for banburying at a temperature of 120-140 DEG C for 8-15 min, then adding a foaming agent AC and a crosslinking agent DCP, and continuously banburying for 3-8 min to obtain banburyed material; carrying out open milling and foaming molding on the banburyed material, and finally placing and curing for 12-18 h to obtain the EVA composite foaming material. The product prepared by the application has the performance coordination of mechanical properties, elongation at break and compression permanent deformation, and the product has different degrees of ultraviolet stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of EVA foaming technology, specifically to an EVA composite foaming material and its preparation method. Background Technology

[0002] EVA foam material, due to its excellent performance, has industrial applications in footwear, toys, padding, nail and beauty products, elastic cushioning, and decorative materials. EVA foam material is produced using a large-sheet foaming process. After mixing, open mixing, and sheeting, it is hot-pressed in a mold to obtain large foam sheets, which are then processed into various products through slicing, punching, and trimming. While the scraps generated during existing EVA foam slicing processes are recycled, they often lead to deterioration in the mechanical properties, elongation at break, and compression set of the products. Furthermore, the products exhibit poor UV stability to varying degrees, limiting their usability. Summary of the Invention

[0003] In view of the deficiencies of the prior art, the purpose of this invention is to provide an EVA composite foaming material and its preparation method to solve the problems mentioned in the background art.

[0004] The present invention solves the technical problem by adopting the following technical solution: This invention provides a method for preparing EVA composite foam material, comprising the following steps: Step 1: Weigh out the raw materials according to the specified portions: 40-60 parts EVA, 10-20 parts ethylene-octene copolymer, 5-15 parts EPDM rubber, 5-10 parts hydrogenated styrene-butadiene-styrene block copolymer, 5-15 parts low-density polyethylene, 10-30 parts EVA foaming waste powder, 2-5 parts foaming agent AC, 0.5-1.5 parts crosslinking agent DCP, 5-8 parts functional additives, 4-7 parts graphene modifier, 0.5-1.5 parts zinc stearate, and 0.3-1 parts stearic acid; Step 2: EVA, ethylene-octene copolymer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer, low-density polyethylene, EVA foaming waste powder, functional additives, graphene modifier, zinc stearate, and stearic acid are fed into an internal mixer and mixed at 120-140℃ for 8-15 minutes. Then, foaming agent AC and crosslinking agent DCP are added, and the mixing continues for 3-8 minutes to obtain the mixed material. Step 3: The intensively mixed material is then subjected to open mixing, foaming and molding, and finally left to stand for curing for 12-18 hours to obtain EVA composite foam material.

[0005] Preferably, the VA content in the EVA is 18-28%, and the melt index is 2-8 g / 10 min (190℃, 2.16 kg). The ethylene-octene copolymer has an octene content of 20-40% and a melt index of 1-5 g / 10 min (190℃, 2.16 kg); the hydrogenated styrene-butadiene-styrene block copolymer has a styrene content of 30-40% and a melt index of 1-10 g / 10 min (230℃, 5 kg). The EVA foaming waste powder is EVA foaming waste powder with a particle size of 200 mesh obtained by crushing, grinding and sieving the waste material from the edge cutting of EVA foaming large plates. The EVA foamed large board trimming waste comprises, by part: 90 parts EVA resin, 8 parts inorganic filler and 2 parts processing aid, wherein the inorganic filler is calcium carbonate and the processing aid is zinc stearate. The melt index of the low-density polyethylene is 2-10 g / 10 min (190℃, 2.16 kg).

[0006] Preferably, in step three, the internal mixing material is fed to the rubber mixing mill and passed through it 3-6 times at a temperature of 100-120°C. The roller gap of the rubber mixing mill is 0.5-1.5mm and the roller temperature is 100-110°C. Then, it is pressed into a sheet with a thickness of 1-3mm by the sheet extruder. Foaming molding is carried out by hot pressing foaming at a temperature of 160-180℃ and a pressure of 8-15MPa for 10-25 minutes using a foaming machine.

[0007] Preferably, the preparation method of the functional additive is as follows: S1: By weight, 2-4 parts of β-cyclodextrin, 1-3 parts of metakaolin and 5-8 parts of hollow glass microspheres are mixed evenly to obtain an additive solution based on hollow glass microspheres. S2: By weight, 3-5 parts of sodium silicate solution, 2-4 parts of nano-hydroxyapatite and 2-5 parts of mullite whiskers are thoroughly mixed to obtain modified sodium silicate agent. The additive solution based on hollow glass microspheres and the modified sodium silicate agent were mixed and ball-milled at a weight ratio of (6-8):3. After ball milling, the mixture was filtered and dried to obtain the functional additive.

[0008] The functional additives are formulated and optimized using β-cyclodextrin, metakaolin, and hollow glass microspheres. Sodium silicate solution, nano-hydroxyapatite, and mullite whiskers are added for synergistic effects. Through this co-regulation of raw materials, the functional additives optimize the product's functional coordination and stability within the system. The hollow glass microsphere solution is formulated by blending hollow glass microspheres, sodium lignosulfonate, and sodium alginate solution, with carbon nanotube modifiers added for further co-regulation. The carbon nanotubes in the carbon nanotube modifier are made from silicon carbide, 2-5% (w / w) dopamine hydrochloride solution, and boron oxide. Through this optimization of raw materials, the functional additives further enhance the product's performance coordination and stability within the system, optimizing the product's mechanical properties, elongation at break, and compression set, while also improving the product's resistance to varying degrees of UV stability.

[0009] Preferably, the sodium silicate solution has a mass fraction of 2-5%.

[0010] Preferably, the hollow glass microsphere liquid is prepared by mixing 2-5 parts of hollow glass microspheres, 1-4 parts of sodium lignosulfonate and 2-5 parts of sodium alginate solution evenly by weight, and then adding 1-3 parts of carbon nanotube modifier and stirring evenly to obtain hollow glass microsphere liquid.

[0011] Preferably, the carbon nanotube modifier is prepared by mixing 3-5 parts carbon nanotubes, 2-5 parts silicon carbide, 3-5 parts of a 2-5% (w / w) dopamine hydrochloride solution and 2-3 parts boron oxide thoroughly by weight, then filtering and drying to obtain the carbon nanotube modifier.

[0012] Preferably, the sodium alginate solution has a mass fraction of 2-5%.

[0013] Preferably, the graphene modifier is prepared by: S11: By weight, 3-5 parts of nano-alumina, 2-4 parts of lanthanum oxide, 1-3 parts of basalt fiber, and 5-8 parts of chitosan solution with a mass fraction of 5-8% are thoroughly mixed to obtain the modified solution; S12: Preheat graphene at 55-60℃ for 1 hour to obtain preheated graphene; mix the preheated graphene and the modification liquid at a weight ratio of 3:(5-7) and stir for 1 hour at a stirring speed of 350-450 r / min. After stirring, filter and dry to obtain graphene modifier.

[0014] The graphene modifier is made by preheating graphene and then stirring it with a modifying liquid. The nano-alumina, lanthanum oxide, basalt fiber and chitosan solution with a mass fraction of 5-8% in the modifying liquid work together to improve the product. Through the coordination and optimization of the raw materials, the resulting graphene modifier further enhances the product's functionality, and the product's performance coordination and stability are further improved.

[0015] The present invention also provides an EVA composite foam material, which is prepared by the method for preparing the EVA composite foam material.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The materials of this invention use EVA, ethylene-octene copolymer, EPDM rubber and other matrix raw materials combined with EVA foaming waste powder, and add functional additives and graphene modifiers to improve each other. Through the mutual coordination and optimization of the raw materials, the products have coordinated mechanical properties, elongation at break and compression set, and are resistant to different degrees of ultraviolet stability. Detailed Implementation

[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Example 1: A method for preparing an EVA composite foam material, comprising the following steps: Step 1: Weigh out the raw materials according to the specified portions: 40 parts EVA, 10 parts ethylene-octene copolymer, 5 parts EPDM rubber, 5 parts hydrogenated styrene-butadiene-styrene block copolymer, 5 parts low-density polyethylene, 10 parts EVA foaming waste powder, 2 parts foaming agent AC, 0.5 parts crosslinking agent DCP, 5 parts functional additives, 4 parts graphene modifier, 0.5 parts zinc stearate, and 0.3 parts stearic acid; Step 2: EVA, ethylene-octene copolymer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer, low-density polyethylene, EVA foaming waste powder, functional additives, graphene modifier, zinc stearate, and stearic acid are fed into an internal mixer and internally mixed at 120°C for 8 minutes. Then, foaming agent AC and crosslinking agent DCP are added, and the mixing continues for 3 minutes to obtain the mixed material. Step 3: The mortar is subjected to open mixing, foaming and molding, and finally left to stand for 12 hours to obtain EVA composite foam material.

[0019] In this embodiment, the VA content of EVA is 18%, and the melt index is 2g / 10min (190℃, 2.16kg). The ethylene-octene copolymer has an octene content of 20% and a melt index of 1 g / 10 min (190℃, 2.16 kg); the hydrogenated styrene-butadiene-styrene block copolymer has a styrene content of 30% and a melt index of 1 g / 10 min (230℃, 5 kg). The EVA foaming waste powder is EVA foaming waste powder with a particle size of 200 mesh obtained by crushing, grinding and sieving the waste material from the edge cutting of EVA foaming large plates. The EVA foamed large board trimming waste comprises, by part: 90 parts EVA resin, 8 parts inorganic filler and 2 parts processing aid, wherein the inorganic filler is calcium carbonate and the processing aid is zinc stearate. The melt index of the low-density polyethylene is 2 g / 10 min (190 °C, 2.16 kg).

[0020] In step three of this embodiment, the internal mixing material is fed to the rubber mixing mill and passed through it three times at a temperature of 100°C. The roller gap of the rubber mixing mill is 0.5 mm and the roller temperature is 100°C. Then, it is pressed into a sheet with a thickness of 1 mm by the sheet extruder. The foaming process involves hot-pressing the foam at 160℃ and 8MPa pressure for 10 minutes using a foaming machine.

[0021] The preparation method of the functional additive in this embodiment is as follows: S1: By weight, 2 parts of β-cyclodextrin, 1 part of metakaolin and 5 parts of hollow glass microspheres are mixed evenly to obtain an additive solution based on hollow glass microspheres. S2: By weight, 3 parts sodium silicate solution, 2 parts nano hydroxyapatite and 2 parts mullite whiskers are thoroughly mixed to obtain modified sodium silicate agent. The additive solution based on hollow glass microspheres and the modified sodium silicate agent were mixed and ball-milled at a weight ratio of 6:3. After ball milling, the mixture was filtered and dried to obtain the functional additive.

[0022] The sodium silicate solution in this embodiment has a mass fraction of 2%.

[0023] The preparation method of hollow glass microsphere liquid in this embodiment is as follows: by weight, 2 parts of hollow glass microspheres, 1 part of sodium lignosulfonate and 2 parts of sodium alginate solution are mixed evenly, and then 1 part of carbon nanotube modifier is added and stirred evenly to obtain hollow glass microsphere liquid.

[0024] The preparation method of the carbon nanotube modifier in this embodiment is as follows: by weight, 3 parts carbon nanotubes, 2 parts silicon carbide, 3 parts 2% (w / w) dopamine hydrochloride solution and 2 parts boron oxide are mixed thoroughly, then filtered and dried to obtain the carbon nanotube modifier.

[0025] The sodium alginate solution in this embodiment has a mass fraction of 2%.

[0026] The preparation method of the graphene modifier in this embodiment is as follows: S11: By weight, 3 parts of nano-alumina, 2 parts of lanthanum oxide, 1 part of basalt fiber, and 5 parts of chitosan solution with a mass fraction of 5% are thoroughly mixed to obtain the modified solution; S12: Preheat graphene at 55℃ for 1 hour to obtain preheated graphene; mix the preheated graphene and the modification liquid at a weight ratio of 3:5 and stir for 1 hour at a stirring speed of 350 r / min. After stirring, filter and dry to obtain graphene modifier.

[0027] This embodiment also provides an EVA composite foaming material, which is prepared by the above-described method for preparing EVA composite foaming materials.

[0028] Example 2: A method for preparing an EVA composite foam material, comprising the following steps: Step 1: Weigh out the raw materials according to the specified portions: 60 parts EVA, 20 parts ethylene-octene copolymer, 15 parts EPDM rubber, 10 parts hydrogenated styrene-butadiene-styrene block copolymer, 15 parts low-density polyethylene, 30 parts EVA foaming waste powder, 5 parts foaming agent AC, 1.5 parts crosslinking agent DCP, 8 parts functional additives, 7 parts graphene modifier, 1.5 parts zinc stearate, and 1 part stearic acid; Step 2: EVA, ethylene-octene copolymer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer, low-density polyethylene, EVA foaming waste powder, functional additives, graphene modifier, zinc stearate, and stearic acid are fed into an internal mixer and internally mixed at 140°C for 15 minutes. Then, foaming agent AC and crosslinking agent DCP are added, and the mixing continues for 8 minutes to obtain the mixed material. Step 3: The intensively mixed material is subjected to open mixing, foaming and molding, and finally left to stand and cure for 18 hours to obtain EVA composite foam material.

[0029] In this embodiment, the VA content of EVA is 28%, and the melt index is 8g / 10min (190℃, 2.16kg). The ethylene-octene copolymer has an octene content of 40% and a melt index of 5 g / 10 min (190℃, 2.16 kg); the hydrogenated styrene-butadiene-styrene block copolymer has a styrene content of 40% and a melt index of 10 g / 10 min (230℃, 5 kg). The EVA foaming waste powder is EVA foaming waste powder with a particle size of 200 mesh obtained by crushing, grinding and sieving the waste material from the edge cutting of EVA foaming large plates. The EVA foamed large board trimming waste comprises, by part: 90 parts EVA resin, 8 parts inorganic filler and 2 parts processing aid, wherein the inorganic filler is calcium carbonate and the processing aid is zinc stearate. The low-density polyethylene has a melt index of 10 g / 10 min (190 °C, 2.16 kg).

[0030] In step three of this embodiment, the internal mixing material is fed to the rubber mixing mill and passed through it 6 times at a temperature of 120°C. The roller gap of the rubber mixing mill is 1.5mm and the roller temperature is 110°C. Then it is pressed into a sheet with a thickness of 3mm by the sheet extruder. The foaming process involves hot-pressing the foam at 180℃ and 15MPa pressure for 25 minutes using a foaming machine.

[0031] The preparation method of the functional additive in this embodiment is as follows: S1: By weight, 4 parts of β-cyclodextrin, 3 parts of metakaolin and 8 parts of hollow glass microspheres are mixed evenly to obtain an additive solution based on hollow glass microspheres. S2: By weight, 5 parts sodium silicate solution, 4 parts nano hydroxyapatite and 5 parts mullite whiskers are thoroughly mixed to obtain modified sodium silicate agent. The additive solution based on hollow glass microspheres and the modified sodium silicate agent were mixed and ball-milled at a weight ratio of 8:3. After ball milling, the mixture was filtered and dried to obtain the functional additive.

[0032] The sodium silicate solution in this embodiment has a mass fraction of 5%.

[0033] The preparation method of hollow glass microsphere liquid in this embodiment is as follows: 5 parts hollow glass microspheres, 4 parts sodium lignosulfonate and 5 parts sodium alginate solution are mixed evenly by weight, and then 3 parts carbon nanotube modifier are added and stirred evenly to obtain hollow glass microsphere liquid.

[0034] The preparation method of the carbon nanotube modifier in this embodiment is as follows: by weight, 5 parts carbon nanotubes, 5 parts silicon carbide, 5 parts 5% (w / w) dopamine hydrochloride solution and 3 parts boron oxide are mixed thoroughly, then filtered and dried to obtain the carbon nanotube modifier.

[0035] The sodium alginate solution in this embodiment has a mass fraction of 5%.

[0036] The preparation method of the graphene modifier in this embodiment is as follows: S11: By weight, 5 parts of nano-alumina, 4 parts of lanthanum oxide, 3 parts of basalt fiber and 8 parts of chitosan solution with a mass fraction of 8% are thoroughly mixed to obtain the modified liquid; S12: Preheat graphene at 60℃ for 1 hour to obtain preheated graphene; mix the preheated graphene and the modification liquid at a weight ratio of 3:7 and stir for 1 hour at a stirring speed of 450 r / min. After stirring, filter and dry to obtain graphene modifier.

[0037] This embodiment also provides an EVA composite foaming material, which is prepared by the above-described method for preparing EVA composite foaming materials.

[0038] Example 3: A method for preparing an EVA composite foam material, comprising the following steps: Step 1: Weigh out the raw materials according to the specified portions: 50 parts EVA, 15 parts ethylene-octene copolymer, 10 parts EPDM rubber, 7.5 parts hydrogenated styrene-butadiene-styrene block copolymer, 10 parts low-density polyethylene, 20 parts EVA foaming waste powder, 3.5 parts foaming agent AC, 1.0 part crosslinking agent DCP, 6.5 parts functional additives, 5.5 parts graphene modifier, 1.0 part zinc stearate, and 0.6 parts stearic acid; Step 2: EVA, ethylene-octene copolymer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer, low-density polyethylene, EVA foaming waste powder, functional additives, graphene modifier, zinc stearate, and stearic acid are fed into an internal mixer and mixed at 130°C for 11 minutes. Then, foaming agent AC and crosslinking agent DCP are added, and the mixing continues for 5.5 minutes to obtain the mixed material. Step 3: The intensively mixed material is subjected to open mixing, foaming and molding, and finally left to stand and cure for 15 hours to obtain EVA composite foam material.

[0039] In this embodiment, the VA content of EVA is 20%, and the melt index is 4g / 10min (190℃, 2.16kg). The ethylene-octene copolymer has an octene content of 30% and a melt index of 3 g / 10 min (190℃, 2.16 kg); the hydrogenated styrene-butadiene-styrene block copolymer has a styrene content of 35% and a melt index of 5 g / 10 min (230℃, 5 kg). The EVA foaming waste powder is EVA foaming waste powder with a particle size of 200 mesh obtained by crushing, grinding and sieving the waste material from the edge cutting of EVA foaming large plates. The EVA foamed large board trimming waste comprises, by part: 90 parts EVA resin, 8 parts inorganic filler and 2 parts processing aid, wherein the inorganic filler is calcium carbonate and the processing aid is zinc stearate. The low-density polyethylene has a melt index of 6 g / 10 min (190 °C, 2.16 kg).

[0040] In step three of this embodiment, the internal mixing material is fed to the rubber mixing mill and passed through it four times at a temperature of 110°C. The roller gap of the rubber mixing mill is 1.0 mm and the roller temperature is 105°C. Then, it is pressed into a sheet with a thickness of 2 mm by the sheet extruder. The foaming process involves hot-pressing the foam at 170℃ and 11MPa for 15 minutes using a foaming machine.

[0041] The preparation method of the functional additive in this embodiment is as follows: S1: By weight, 3 parts of β-cyclodextrin, 2 parts of metakaolin and 6.5 parts of hollow glass microsphere liquid are mixed evenly to obtain the additive liquid based on hollow glass microspheres; S2: By weight, 4 parts sodium silicate solution, 3 parts nano hydroxyapatite and 3.5 parts mullite whiskers are thoroughly mixed to obtain modified sodium silicate agent; The additive solution based on hollow glass microspheres and the modified sodium silicate agent were mixed and ball-milled at a weight ratio of 7:3. After ball milling, the mixture was filtered and dried to obtain the functional additive.

[0042] The sodium silicate solution in this embodiment has a mass fraction of 3.5%.

[0043] The preparation method of the hollow glass microsphere liquid in this embodiment is as follows: 3.5 parts of hollow glass microspheres, 2.5 parts of sodium lignosulfonate and 3.5 parts of sodium alginate solution are mixed evenly according to weight, and then 2 parts of carbon nanotube modifier are added and stirred evenly to obtain hollow glass microsphere liquid.

[0044] The preparation method of the carbon nanotube modifier in this embodiment is as follows: by weight, 4 parts of carbon nanotubes, 3.5 parts of silicon carbide, 4 parts of 3.5% (w / w) dopamine hydrochloride solution and 2.5 parts of boron oxide are mixed thoroughly, then filtered and dried to obtain the carbon nanotube modifier.

[0045] The sodium alginate solution in this embodiment has a mass fraction of 3.5%.

[0046] The preparation method of the graphene modifier in this embodiment is as follows: S11: By weight, 4 parts of nano-alumina, 3 parts of lanthanum oxide, 2 parts of basalt fiber, and 6.5 parts of chitosan solution with a mass fraction of 6.5% are thoroughly mixed to obtain the modified solution; S12: Preheat graphene at 58℃ for 1 hour to obtain preheated graphene; mix the preheated graphene and the modification liquid at a weight ratio of 3:6 and stir for 1 hour at a stirring speed of 400 r / min. After stirring, filter and dry to obtain graphene modifier.

[0047] This embodiment also provides an EVA composite foaming material, which is prepared by the above-described method for preparing EVA composite foaming materials.

[0048] Comparative Example 1: Unlike Example 3, no functional additives were added.

[0049] Comparative Example 2: Unlike Example 3, no modified sodium silicate agent was added during the preparation of the functional additive.

[0050] Comparative Example 3: Unlike Example 3, β-cyclodextrin and metakaolin were not added in the preparation of the additive solution based on hollow glass microspheres.

[0051] Comparative Example 4: Unlike Example 3, no carbon nanotube modifier was added in the preparation of the hollow glass microsphere liquid.

[0052] Comparative Example 5: Unlike Example 3, silicon carbide and boron oxide were not added in the preparation of the carbon nanotube modifier.

[0053] Comparative Example 6: Unlike Example 3, no graphene modifier was added.

[0054] Comparative Example 7: Unlike Example 3, no modifying liquid was added during the preparation of the graphene modifier.

[0055] Comparative Example 8: Unlike Example 3, basalt fibers were not added during the preparation of the modified liquid.

[0056] The products of Examples 1-3 and Comparative Examples 1-8 were subjected to performance tests. The mechanical properties, elongation at break, and compression set of the products were tested under both conventional and ultraviolet radiation conditions. The ultraviolet radiation conditions were: using a UVA-340 lamp source, with an irradiance of 10 W / (m²). 2 ·nm), continuous irradiation for 72 hours; using a UVA-340 lamp source, irradiance 50W / (m 2 (·nm), continuous irradiation for 72h); the test results are shown in Table 1.

[0057] Table 1 Product performance test results:

[0058] As can be seen from Comparative Examples 1-8 and Examples 1-3, the product of Example 3 exhibits excellent mechanical properties, elongation at break, and compression set, while also demonstrating varying degrees of UV stability. In contrast, the present invention, without the addition of any functional additive or graphene modifier, shows a trend of deterioration in product performance, particularly under high UV weathering conditions, where the stability deteriorates significantly. Furthermore, the functional additive preparation did not include modified sodium silicate, the preparation of the hollow glass microsphere-based additive solution did not include β-cyclodextrin and metakaolin, and the preparation of the hollow glass microsphere solution did not include carbon nanotube modifiers. In the preparation of modifiers without the addition of silicon carbide and boron oxide, the performance of the products tends to deteriorate to varying degrees. The functional additives obtained by the specific method of this invention have the most significant performance effect. At the same time, in the preparation of graphene modifiers without the addition of modifying liquid, and in the preparation of modifying liquids without the addition of basalt fiber, the performance of the products also tends to deteriorate. Only the graphene modifier prepared by the method of this invention has the most significant performance effect. Furthermore, the preparation of raw materials such as the modifying liquid and carbon nanotube modifier of this invention is proprietary. The technical products made using the technical solution of this invention have the best functional effects.

[0059] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0060] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing an EVA composite foam material, characterized in that, Includes the following steps: Step 1: Weigh the raw materials according to their weight proportions: 40-60 parts EVA, 10-20 parts ethylene-octene copolymer, 5-15 parts EPDM rubber, 5-10 parts hydrogenated styrene-butadiene-styrene block copolymer, 5-15 parts low-density polyethylene, 10-30 parts EVA foaming waste powder, 2-5 parts foaming agent AC, 0.5-1.5 parts crosslinking agent DCP, 5-8 parts functional additives, 4-7 parts graphene modifier, 0.5-1.5 parts zinc stearate, and 0.3-1 parts stearic acid; The preparation method of the functional additive is as follows: S1: By weight, 2-4 parts of β-cyclodextrin, 1-3 parts of metakaolin and 5-8 parts of hollow glass microspheres are mixed evenly to obtain an additive solution based on hollow glass microspheres. S2: By weight, 3-5 parts of sodium silicate solution, 2-4 parts of nano-hydroxyapatite and 2-5 parts of mullite whiskers are thoroughly mixed to obtain modified sodium silicate agent. The additive solution based on hollow glass microspheres and the modified sodium silicate agent were mixed and ball-milled at a weight ratio of (6-8):

3. After ball milling, the mixture was filtered and dried to obtain the functional additive. The preparation method of the graphene modifier is as follows: S11: By weight, 3-5 parts of nano-alumina, 2-4 parts of lanthanum oxide, 1-3 parts of basalt fiber, and 5-8 parts of chitosan solution with a mass fraction of 5-8% are thoroughly mixed to obtain the modified solution; S12: Preheat graphene at 55-60℃ for 1 hour to obtain preheated graphene; mix the preheated graphene and the modification liquid at a weight ratio of 3:(5-7) and stir for 1 hour at a stirring speed of 350-450 r / min. After stirring, filter and dry to obtain graphene modifier. Step 2: EVA, ethylene-octene copolymer, EPDM rubber, hydrogenated styrene-butadiene-styrene block copolymer, low-density polyethylene, EVA foaming waste powder, functional additives, graphene modifier, zinc stearate, and stearic acid are fed into an internal mixer and mixed at 120-140℃ for 8-15 minutes. Then, foaming agent AC and crosslinking agent DCP are added, and the mixing continues for 3-8 minutes to obtain the mixed material. Step 3: The intensively mixed material is then subjected to open mixing, foaming and molding, and finally left to stand for curing for 12-18 hours to obtain EVA composite foam material.

2. The method for preparing an EVA composite foam material according to claim 1, characterized in that, The EVA contains 18-28% VA and has a melt index of 2-8 g / 10 min (190℃, 2.16 kg). The ethylene-octene copolymer has an octene content of 20-40% and a melt index of 1-5 g / 10 min (190℃, 2.16 kg); the hydrogenated styrene-butadiene-styrene block copolymer has a styrene content of 30-40% and a melt index of 1-10 g / 10 min (230℃, 5 kg). The EVA foaming waste powder is EVA foaming waste powder with a particle size of 200 mesh obtained by crushing, grinding and sieving the waste material from the edge cutting of EVA foaming large plates. The EVA foamed large board trimming waste comprises, by part: 90 parts EVA resin, 8 parts inorganic filler and 2 parts processing aid, wherein the inorganic filler is calcium carbonate and the processing aid is zinc stearate. The melt index of the low-density polyethylene is 2-10 g / 10 min (190℃, 2.16 kg).

3. The method for preparing an EVA composite foam material according to claim 1, characterized in that, In step three, during the open mixing process, the internal mixing material is fed to the rubber mixing mill and passed through it 3-6 times at a temperature of 100-120℃. The roller gap of the rubber mixing mill is 0.5-1.5mm and the roller temperature is 100-110℃. Then, it is pressed into sheets with a thickness of 1-3mm by the sheet extruder. Foaming molding is carried out by hot pressing foaming at a temperature of 160-180℃ and a pressure of 8-15MPa for 10-25 minutes using a foaming machine.

4. The method for preparing an EVA composite foam material according to claim 1, characterized in that, The sodium silicate solution has a mass fraction of 2-5%.

5. The method for preparing an EVA composite foam material according to claim 1, characterized in that, The hollow glass microsphere liquid is prepared by mixing 2-5 parts of hollow glass microspheres, 1-4 parts of sodium lignosulfonate and 2-5 parts of sodium alginate solution evenly by weight, and then adding 1-3 parts of carbon nanotube modifier and stirring evenly to obtain hollow glass microsphere liquid.

6. The method for preparing an EVA composite foam material according to claim 5, characterized in that, The preparation method of the carbon nanotube modifier is as follows: by weight, 3-5 parts of carbon nanotubes, 2-5 parts of silicon carbide, 3-5 parts of 2-5% (w / w) dopamine hydrochloride solution and 2-3 parts of boron oxide are thoroughly mixed, then filtered and dried to obtain the carbon nanotube modifier.

7. The method for preparing an EVA composite foam material according to claim 5, characterized in that, The sodium alginate solution has a mass fraction of 2-5%.

8. An EVA composite foam material, characterized in that, It is prepared by the method of any one of claims 1-7 for the preparation of EVA composite foam material.